P-P10 The survival benefit of pancreatic enzyme replacement therapy in adult patients undergoing treatment of pancreatic neuroendocrine tumours. (16th December 2021) - Thompson, Oscar; Hall, Lewis; Roberts, Keith; Shah, Tahir; Bradley, Elizabeth; Powell-Brett, Sarah; Pande, Rupaly
Abstract: Background: Patients with pancreatic neuroendocrine tumours (pNETs), treated with somatostatin analogues (SSAs) or pancreaticoduodenectomy, are at risk of exocrine pancreatic insufficiency. This is frequently undiagnosed but can be treated with pancreatic enzyme replacement therapy (PERT). PERT improves survival and nutritional status in other exocrine pancreatic insufficiency-associated conditions such as pancreatic adenocarcinoma. This single-centre retrospective cohort study aimed to establish whether PERT increases survival or weight maintenance in SSA or pancreaticoduodenectomy-treated patients with pNETs. Methods: Departmental databases identified patients (n = 82) diagnosed with pNETs between 2009 and 2019 and managed with SSAs and/or pancreaticoduodenectomy. Their baseline characteristics, treatments and outcomes were established from clinical records. Cases (n = 47) received PERT 3 months after either pancreaticoduodenectomy or commencement of SSAs, controls (n = 35) did not. Overall survival was analysed using the Kaplan-Meier method, the log-rank test and multivariable Cox regression. Percentage monthly weight changes were compared using the Mann-Witney U test. The cohort was investigated as a whole and stratified by intervention (pancreaticoduodenectomy or SSAs) as more cases having undergone pancreaticoduodenectomy was a potential confounder. Results: Median survival was not reached in either group. Cases experienced significantly greater 5-year overall survival (81% vs 53%, p = 0.010), however, PERT was not independently associated with survival (Hazard ratio 0.47, 95% CI 0.17-1.30, p = 0.143). Cases showed superior median weight maintenance (+0.04% vs -0.10% per month, p = 0.013), but had lower mean baseline weights (70.0kg vs 81.9kg, p = 0.003). Considering SSA-treated patients (n = 55) only, cases (n = 27) showed greater median weight maintenance (+0.04% vs -0.21% per month, p = 0.025) and a trend towards improved median overall survival (55.5, 95% CI 10.3-100.7 vs 47.7, 95% CI 19.1-76.4 months, p = 0.054). Conclusions: PERT may improve the maintenance of weight and therefore nutrition in patients with pNETs, treated with SSAs or pancreaticoduodenectomy. PERT may also convey a survival benefit in this same population, however, due to the numerous factors which affect survival, this study appears underpowered to reliably explore this outcome. Further studies are required to accurately define the use and benefits of PERT in this population.